2012
DOI: 10.1016/j.neuroscience.2012.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of acute and regular physical exercise on cognition and affect

Abstract: The effects of regular exercise versus a single bout of exercise on cognition, anxiety, and mood were systematically examined in healthy, sedentary young adults who were genotyped to determine brain-derived neurotrophic factor (BDNF) allelic status (i.e., Val-Val or Val66Met polymorphism). Participants were evaluated on novel object recognition (NOR) memory and a battery of mental health surveys before and after engaging in either a) a four-week exercise program, with exercise on the final test day, b) a four-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
150
0
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(175 citation statements)
references
References 69 publications
7
150
0
18
Order By: Relevance
“…A large body of evidence shows that exercise can produce benefits on mood and stress [39][40][41]. We did not measure what specific activities participants were doing when they reported leisure, but research suggests that some of the participants' reported leisure activities may have been exercisedbased [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence shows that exercise can produce benefits on mood and stress [39][40][41]. We did not measure what specific activities participants were doing when they reported leisure, but research suggests that some of the participants' reported leisure activities may have been exercisedbased [13].…”
Section: Discussionmentioning
confidence: 99%
“…When individuals engage in exercise, compared to when they do not, their heart rate increases [15,16]; exercise has also shown positive effects on improving positive mood, decreasing negative mood, and lowering stress [39][40][41]. For example, negative mood decreased and vigor increased after an aerobic exercise dance class compared to 15 min before the exercise [41].…”
Section: Dynamic Indices Of Healthmentioning
confidence: 99%
“…The role of exercise on adult cognition has been extensively researched (for reviews see Lambourne & Tomporowski, 2010;Tomporowski, 2003), with cognitive performance assessed during exercise (McMorris & Graydon, 1996), following acute exercise (Coles & Tomporowski, 2008;Hopkins, Davis, & Vantieghem, 2012;Tomporowski, et al, 2005), and following long-term exercise exposure (e.g. Castelli, Hillman, Buck & Erwin, 2007;Hopkins et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Castelli, Hillman, Buck & Erwin, 2007;Hopkins et al, 2012). These effects might be explained in terms of increased cerebral blood flow (Delp, et al, 2001) and heightened arousal due to exercise-induced changes in metabolic rate and reallocation of mental resources (Audiffren, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of healthy humans have found positive effects of exercise on cognitive measures in both children, younger adults, and elderly populations (see e.g. Guiney and Machado 2013, Hopkins et al 2012, Khan and Hillman 2014. Furthermore, findings from human studies suggest a beneficial effect of physical exercise regarding prevention of age-related cognitive impairment and potentially even development of Alzheimer's disease (Erickson et al 2011, Laurin et al 2001, Lindsay et al 2002.…”
Section: Introductionmentioning
confidence: 99%